2016
DOI: 10.1021/acs.jpca.6b07611
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Chiral Symmetry Breaking in Alanine

Abstract: We introduce a general theoretical approach for the simulation of photochemical dynamics under the influence of circularly polarized light to explore the possibility of generating enantiomeric enrichment through polarized-light-selective photochemistry. The method is applied to the simulation of the photolysis of alanine, a prototype chiral amino acid. We show that a systematic enantiomeric enrichment can be obtained depending on the helicity of the circularly polarized light that induces the excited-state pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…In agreement with the experiment on absorption of circularly polarized UV light, the molecular dynamics simulations based on the gradients obtained from the semi-empirical multireference OM2/MRCI method 897 have shown that photolysis leads to enantiomeric enrichment of either right-or left-handed enantiomer depending on the helicity of the laser field.…”
Section: Isolated Amino Acids and Small Peptide Modelssupporting
confidence: 78%
“…In agreement with the experiment on absorption of circularly polarized UV light, the molecular dynamics simulations based on the gradients obtained from the semi-empirical multireference OM2/MRCI method 897 have shown that photolysis leads to enantiomeric enrichment of either right-or left-handed enantiomer depending on the helicity of the laser field.…”
Section: Isolated Amino Acids and Small Peptide Modelssupporting
confidence: 78%
“…It is known that α-alanine has UV absorption bands located at ∼270 nm (4.59 eV, hereafter we refer to this state as S 1 ), 220 nm (5.64 eV, S 2 ), 190 nm (6.53 eV, S 3 ), and more at shorter wavelengths, with the S 2 band having the strongest absorbance of the three. , Numerous experimental and theoretical studies on the photodynamics of alanine have been reported, particularly focusing on enantioselective dissociations that lead to enantiomeric enrichment. However, the main photoproducts of alanine dissociation have not been directly identified. In this work, we have investigated the photodissociation dynamics of α-alanine and its deuterated species in the S 1 and S 2 excited states in a p H 2 matrix.…”
mentioning
confidence: 99%
“…33 and 64 and later adapted to ADC(2). 65 The classical nuclear dynamics was simulated by integration of Newton's equations of motion using the velocity Verlet algorithm 66 with an integration time step of 0.2 fs. Considering the ground and the three energetically lowest excited states, the electronic population dynamics was determined along the classical trajectories by solving the time-dependent Schrödinger equation including the non-adiabatic couplings between all electronic states.…”
Section: Methodsmentioning
confidence: 99%